Comparison between mechanical and manual manuring towards cost and labour saving in oil palm plantation / Iqbal Hakeem Shamsuri - Shamsuri, Iqbal Hakeem (Faculty of Plantation and Agrotechnology, 2018)
The research was run to compare which fertilizer application technique is more efficient in terms of productivity of each day of manuring program and lower cost including variable cost and fixed cost of each techniques. The test was run in an area where mechanical spreader is applicable and also manual technique with a team of 5 workers in applying fertilizer. The type of fertilizer used in this study was Ammonia Sulphate (AS) fertilizer which was one of the main fertilizer to supply sufficient nitrogen (N) nutrient to each matured palm. The study found out that mechanical spreader has higher average of productivity; 154 Bag/day, compared to manual; 96 Bag/day. The cost per hectare also shows that mechanical spreader; RM5.44/ha, is lower compared to manual; RM8.09/ha. Moreover, the hectare coverage per day shows that mechanical; 38.8Ha/day, is more efficient compared to manual; 24.2Ha/day. Lastly, the average workers used by mechanical (2 workers/day) is lower that using manual which need (5 workers/day).